Validation of Social Skills Measurement Tools for Special Needs Student - Farida Kurniawati (The Center for Disability Studies and Services Brawijaya University, 2019)
The adaptation process for measurement of special needs student's social skills in inclusive primary schools was reported in this study. The Social Skills Improvement System was tested on 108 students aged 6-12 years. Social skills measurement include seven dimensions, that are empathy, cooperation, assertiveness, communication, self-control, participation, and responsibility. The adaptation process includes translation, back-translation, and expert judgment. Legibility tests then were conducted on 10 students with special needs. Reliability test shows that the measurement has an Alpha value of 0.833. Confirmatory Factor Analysis is done to see the loading factor of each item in the measuring instrument for students with special needs in inclusive primary schools. It was found that 24 items (three items with a loading factor below the good value is preserved) in the instrument had a factor loading ranging between 0.04-0.70 (RMSEA = 0.063, IFI = 0.89 and GFI = 0.80). Based on these results, it can be concluded that SSIS measuring instruments that have been adapted into Indonesian is valid and reliable to measure the social skill of special need primary students. The implications of the study findings are discussed for future research. The adaptation process for measurement of special needs student's social skills in inclusive primary schools was reported in this study. The Social Skills Improvement System was tested on 108 students aged 6-12 years. Social skills measurement include seven dimensions, that are empathy, cooperation, assertiveness, communication, self-control, participation, and responsibility. The adaptation process includes translation, back-translation, and expert judgment. Legibility tests then were conducted on 10 students with special needs. Reliability test shows that the measurement has an Alpha value of 0.833. Confirmatory Factor Analysis is done to see the loading factor of each item in the measuring instrument for students with special needs in inclusive primary schools. It was found that 24 items (three items with a loading factor below the good value is preserved) in the instrument had a factor loading ranging between 0.04-0.70 (RMSEA = 0.063, IFI = 0.89 and GFI = 0.80). Based on these results, it can be concluded that SSIS measuring instruments that have been adapted into Indonesian is valid and reliable to measure the social skill of special need primary students. The implications of the study findings are discussed for future research.